Comparison of rumen bacterial communities between yaks (Bos grunniens) and Qaidam cattle (Bos taurus) fed a low protein diet with different energy levels - Liu, Hu; Ran, Tao; Zhang, Chengfu; Yang, Wenzhu; Wu, Xiukun; Degen, Allan; Long, Ruijun; Shi, Zunji; Zhou, Jianwei (Frontiers in Microbiology, 2022)
The yak (Bos grunniens), an indigenous bovine on the Qinghai-Tibetan plateau (QTP), is reported to digest low quality forage to a greater extent and to require less protein and energy for maintenance than the introduced Qaidam cattle (Bos taurus). Ruminal bacteria play a major role in feed degradation, and therefore, we hypothesized that ruminal bacteria composition would differ between yaks and cattle, and confer an advantage to yaks for poor quality diets. To test our hypothesis, we determined the ruminal bacteria profiles, rumen fermentation parameters, and enzyme activities in these bovine species consuming a low-protein diet varying in energy levels. Six castrated yaks (155±5.8 kg) and 6 castrated Qaidam cattle (154±8.0 kg) were used in two concurrent 4 × 4 Latin square designs with 2 additional animals of each species in each period. The animals were offered a low-protein diet of 70.4 g/kg dry matter (DM) and one of four metabolizable energy levels, namely 6.62, 8.02, 9.42, and 10.80 MJ/kg. Ruminal pH, concentrations of ammonia-N and total volatile fatty acids (VFAs), the molar proportion of acetate, and the ratio of acetate to propionate (A:P) were greater (P < 0.05), whereas the molar proportion of propionate was lesser (P = 0.043) in yaks than in cattle. With increasing dietary energy level, ruminal pH, the molar proportion of acetate and the ratio of A:P decreased linearly (P < 0.05), whereas concentrations of total VFAs, molar proportions of propionate, butyrate, iso-butyrate, and iso-valerate and concentration of ammonia-N increased linearly (P < 0.05). The relative abundance (RA) of Firmicutes increased linearly (P < 0.01), whereas, of Bacteroidetes decreased linearly (P < 0.001) with increasing energy level in both bovine species. Prevotella and Rikenellaceae_RC9_gut_group decreased linearly (P < 0.05) with increasing energy level in both yaks and cattle. The RA of fibrolytic (e.g. Rikenellaceae_RC9_gut_group), and H2-incorporating bacteria (e.g. Quinella) were greater (P < 0.05) in yaks than in cattle. These results demonstrate that the two bovines differ in ruminal bacterial profiles and rumen fermentation parameters, and confer an advantage to yaks over cattle in consuming a low protein diet with varying energy levels.